A TRIP-assisted dual-phase high-entropy alloy: Grain size and phase fraction effects on deformation behavior. (1st June 2017) - Li, Zhiming; Tasan, Cemal Cem; Pradeep, Konda Gokuldoss; Raabe, Dierk
Abstract: We present a systematic microstructure oriented mechanical property investigation for a newly developed class of transformation-induced plasticity-assisted dual-phase high-entropy alloys (TRIP-DP-HEAs) with varying grain sizes and phase fractions. The DP-HEAs in both, as-homogenized and recrystallized states consist of a face-centered cubic (FCC) matrix containing a high-density of stacking faults and a laminate hexagonal close-packed (HCP) phase. No elemental segregation was observed in grain interiors or at interfaces even down to near-atomic resolution, as confirmed by energy-dispersive X-ray spectroscopy and atom probe tomography. The strength-ductility combinations of the recrystallized DP-HEAs (Fe50 Mn30 Co10 Cr10 ) with varying FCC grain sizes and HCP phase fractions prior to deformation are superior to those of the recrystallized equiatomic single-phase Cantor reference HEA (Fe20 Mn20 Ni20 Co20 Cr20 ). The multiple deformation micro-mechanisms (including strain-induced transformation from FCC to HCP phase) and dynamic strain partitioning behavior among the two phases are revealed in detail. Both, strength and ductility of the DP-HEAs increase with decreasing the average FCC matrix grain size and increasing the HCP phase fraction prior to loading (in the range of 10–35%) due to the resulting enhanced stability of the FCC matrix. These insights are used to project some future directions for designing advanced TRIP-HEAs through the adjustment of the matrix phase's stability by alloy tuning and grain size effects. Graphical abstract: Image